Semiotic Analysis on The Interpretation of The Dark Ages in Anime Orb: on The Movements of The Earth - Ratna Saputri, Niken; Rahmawati, Etika Laili (Dinasti Research, 2025)
Nowadays, the most popular form of animation media is anime, a form of animation media with a unique style that popularized by Japan. This research of semiotic analysis on the interpretation of the Dark Ages in anime Orb: On The Movements Of The Earth aims to find connotative and denotative signs from the anime “Orb: On the Movement of The Earth” related to the interpretation of